2021
DOI: 10.5194/bg-18-5117-2021
|View full text |Cite
|
Sign up to set email alerts
|

The Bouraké semi-enclosed lagoon (New Caledonia) – a natural laboratory to study the lifelong adaptation of a coral reef ecosystem to extreme environmental conditions

Abstract: Abstract. According to current experimental evidence, coral reefs could disappear within the century if CO2 emissions remain unabated. However, recent discoveries of diverse and high cover reefs that already live under extreme conditions suggest that some corals might thrive well under hot, high-pCO2, and deoxygenated seawater. Volcanic CO2 vents, semi-enclosed lagoons, and mangrove estuaries are unique study sites where one or more ecologically relevant parameters for life in the oceans are close to or even w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 123 publications
0
64
0
Order By: Relevance
“…All presently reported CMC habitats in the literature occur at a shallow depth and are microtidal (≤2 m) [ 36 , 44 , 47 , 48 , 61 , 62 ]. We therefore narrowed down the potential CMC habitat by areas with a tidal amplitude of ≤2 m, since a greater tidal amplitude would lead to prolonged air exposure of corals in this area.…”
Section: Methodsmentioning
confidence: 99%
“…All presently reported CMC habitats in the literature occur at a shallow depth and are microtidal (≤2 m) [ 36 , 44 , 47 , 48 , 61 , 62 ]. We therefore narrowed down the potential CMC habitat by areas with a tidal amplitude of ≤2 m, since a greater tidal amplitude would lead to prolonged air exposure of corals in this area.…”
Section: Methodsmentioning
confidence: 99%
“…Coral populations that can cope with, or recover from, increasingly frequent and intense stress events are critical to the persistence of tropical reefs, and recent efforts to predict the future structure and functioning of reefs have logically focussed on resolving the nature of coral tolerance to acute heating events [5][6][7][8][9][10]. One approach has been to examine coral populations that have adapted to present day extreme environments; for example, warm lagoons [11,12], intertidal pools [13,14] and thermally extreme seas [15,16]. Profiling coral biology from these so-called 'natural laboratories' has shown how numerous factors contribute to high heat tolerance, including rapid modifications in gene expression related to extracellular matrix formation and oxidative stress [17,18], heat-shock protein upregulation [19], but also rapid recovery to a pre-disturbance baseline level of these differentially expressed genes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Corals thriving in mangrove lagoons adjacent to tropical reefs are characterized by particularly extreme environmental conditions. Waters within reef-neighbouring mangrove lagoon habitats can reach 33°C (Woody Isles, Great Barrier Reef) in summer [24], which is well above the tolerance threshold for many reef corals [3], but also experience extensive diel acidification ( pH range 7.2-8.2) and deoxygenation (oxygen range 0.6-7.33 mg l −1 ) [11,25]. Despite these relatively extreme lagoonal conditions, coral populations can thrive through associations with different microbial communities, including both micro-algal endosymbionts (family: Symbiodiniaceae) and bacteria [24,26,27], and exhibit very different metabolic properties compared to the reef corals [12,25,27].…”
Section: Introductionmentioning
confidence: 99%
“…Extreme systems recently identified as ideal sites for studying coral resilience to complex stressor regimes are reef adjacent mangrove lagoons ( Camp et al, 2018 ), which can be inhabited by species of reef-building corals commonly found on nearby reefs ( Macintyre et al, 2000 ; Rogers, 2009 , 2017 ; Camp et al, 2017 , 2019 ; Lord et al, 2020 ). Mangroves can reduce thermal stress by shading corals, but these shallow environments also expose corals to hotter, more acidic and deoxygenated conditions ( Rogers and Herlan, 2012 ; Camp et al, 2017 ; Rogers, 2017 ; Maggioni et al, 2021 ). Compared to adjacent reefs, where pH levels fluctuate between 8.1 and 8.2, mangrove lagoons can exhibit consistently low pH (below 7.8), with daily drops to below 7.3 ( Camp et al, 2017 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%